The Relationship between Diabetes and Periodontal Disease in Thi-Qar province, Iraq - Alazraqi, Adnan Abed Azeez (Journal of Biomedicine and Biochemistry, 2024)
Background and Objective Diabetes not only increases the likeli- hood of developing periodontitis, but periodontitis can also adversely affect the regulation of blood sugar levels, so that in this study, we will find the possible correlations between diabetes and periodontal Disease that may be associated of the risk factor for the patients.Methods The study used 50 patients diabetes and periodontal disease and 50 control The control group consisted of people who appeared to be in good health.Results The results showed the increased severity of the risk factor on the periodontal disease and there are a significant difference at (P.value ≤ 0.05) patients and control group according to the age ,sex and smoke groups and the periodontal Disease in patients was significantly (P.value ≤ 0.05) greater than that of the control and a significant difference find between diabetic and periodontitis was 66% of patients had periodontitis, and 34% had not periodontitis, while in the control group only 16% had periodontitis, and 84% had not periodontitis, Finally, according to gin- givitis, the current results investigated a significant difference at p. value < 0.05, between two groups, was this study recoded 60% of patients had gingivitis, and 40% without gingivitis, while in the control group only 10% had gingivitis, and 90% without gingivitis.